Numerical modeling of the seismic out-of-plane response of a plain and TRM-strengthened rammed earth subassembly. (15th August 2019) - Allahvirdizadeh, Reza; Oliveira, Daniel V.; Silva, Rui A.
Highlights: Seismic performance of the rammed earth components is numerically investigated. A novel advanced simulation procedure for further applications is introduced. Possible failure modes of the rammed earth walls under earthquakes are highlighted. Strengthening by LC-TRM as a compatible and affordable solution is investigated. Knowledge gaps in seismic performance of rammed earth components are addressed. Abstract: The importance of raw earth is highlighted by the millions of persons living in earthen buildings around the World and by numerous historical monuments made of this material. Its widely availability led to the development of a variety of building techniques, including rammed earth, which is the main focus of this study. Similarly to unreinforced masonry structures, rammed earth buildings acceptably withstand gravity loads, but are significantly vulnerable to earthquakes. In this regard, great attention has been put on the proposal of efficient, compatible, affordable and reversible strengthening solutions. However, very limited studies address either the experimental testing or modeling of the seismic response of such buildings. The current study investigates the seismic out-of-plane performance of a plain and subsequently strengthened rammed earth subassembly (U-shape) using an advanced finite element modeling approach calibrated based on previously conducted small-scale experiments. Here, failure mechanisms, corresponding capacity and efficiency of the adopted strengthening solution (low-cost textile-reinforced mortar) are evaluated by means of pushover analyses. Then, the reliability of the pushover analyses is assessed by comparing its outcomes with that of the incremental dynamic analyses. In general, the failure was found to be governed by overturning of the web wall due to its detachment from the wing walls, while the strengthening was found to increase the capacity and delay the damage development.